Role of RNA m6A modification in titanium dioxide nanoparticle-induced acute pulmonary injury: An in vitro and in vivo study. (15th October 2022) - Ruan, Fengkai; Liu, Changqian; Wang, Yi; Cao, Xisen; Tang, Zhen; Xu, Jiaying; Zeng, Jie; Yin, Hanying; Zheng, Naying; Yang, Chunyan; Zuo, Zhenghong; He, Chengyong
Abstract: RNA N 6 -methyladenosine (m 6 A) modification regulates the cell stress response and homeostasis, but whether titanium dioxide nanoparticle (nTiO2 )-induced acute pulmonary injury is associated with the m 6 A epitranscriptome and the underlying mechanisms remain unclear. Here, the potential association between m 6 A modification and the bioeffects of several engineered nanoparticles (nTiO2, nAg, nZnO, nFe2 O3, and nCuO) were verified thorough in vitro experiments. nFe2 O3, nZnO, and nTiO2 exposure significantly increased the global m 6 A level in A549 cells. Our study further revealed that nTiO2 can induce m 6 A-mediated acute pulmonary injury. Mechanistically, nTiO2 exposure promoted methyltransferase-like 3 (METTL3)-mediated m 6 A signal activation and thus mediated the inflammatory response and IL-8 release through the degeneration of anti-Mullerian hormone ( AMH ) and Mucin5B ( MUC5B ) mRNAs in a YTH m 6 A RNA-binding protein 2 (YTHDF2)-dependent manner. Moreover, nTiO2 exposure stabilized METTL3 protein by the lipid reactive oxygen species (ROS)-activated ERK1/2 pathway. The scavenging of ROS with ferrostatin-1 (Fer-1) alleviates the ERK1/2 activation, m 6 A upregulation, and the inflammatory response caused by nTiO2 both in vitro and in vivo . In conclusion, our study demonstrates that m 6 A is a potential intervention target for alleviating the adverse effects of nTiO2 -induced acute pulmonary injury in vitro and in vivo, which has far-reaching implications for protecting human health and improving the sustainability of nanotechnology. Graphical abstract: Image 1 Highlights: nTiO2 exposure changed global m 6 A modification level in A549 and Beas-2B cells. nTiO2 induces acute pulmonary injury through the METTL3-mediated m 6 A upregulation. nTiO2 exposure stabilize METTL3 protein by lipid ROS activated ERK1/2 pathway. ROS/ERK/METTL3/m 6 A pathway determines acute pulmonary injury caused by nTiO2 .